Polarization and Inequality in Spain: 1973-91 - Gradin, Carlos (Journal of Income Distribution®, 2002)
I analyze Spanish expenditure and income distribution during the crucial period of the recovery of democracy in the middle 1970s, after which extensive reforms in political and welfare institutions were conducted. For that purpose, I use two perspectives that do not necessarily agree: the more standard measurement of inequality based on the Lorenz criterion, and the less standard measurement of polarization. The latter accounts for an eventual concentration around the main poles of the distribution and allows us to look at what happened to the underlying groups, such as the middle class and the most extreme groups.